AB1181 The Impact of Physical Function on Patient Global Assessment in Rheumatoid Arthritis. (9th June 2015) - Watanabe, T.; Kojima, T.; Takahashi, N.; Funahashi, K.; Asai, S.; Takemoto, T.; Asai, N.; Ishiguro, N.
Abstract : Background: In 2011 ACR/EULAR Boolean-based definition of remission in RA, patient global assessment (PGA) is often the limiting factor for reaching remission 1 . The main determinants for the PGA are pain, function, and number of swollen joints 2 . Physical functions will affair clinical remission. Given the tight correlation between physical function and loss of social and economic opportunities 3, as well as clinical remission, functional remission is also an important goal. Objectives: The aim of this study is to investigate the impact of physical function on PGA, and to clarify the predicting factor of functional and clinical remission. Methods: 512 RA patients at Nagoya University Hospital were enrolled in this study. Physical function was assessed using Health Assessment Questionnaire (HAQ), disease activity DAS28-CRP, and PGA 0-10 visual analog scale. Results: Patients were primarily women (81.4%). Mean age was 60.3±14.0 years, disease duration 13.0±10.4 years, HAQ-DI 0.67±0.75, and DAS28-CRP 2.37±1.02. HAQ-DI was getting worse in correlation with disease activity (r=0.452), and disease duration (r=0.446). In the early stage of RA (duration <2 years), HAQ-DI was strongly correlated with DAS28-CRP (r=0.758). PGA had a most strong correlation with the HAQ-DI in the components of the DAS28-CRP (r=0.395). Of the patients who were in functional remission (HAQ-DI ≤0.5), mean PGA was 0.51, of the patients whose HQA-DI >0.5; 4.2 (Fig. 1 ). 50.3% of the former fulfilled PGA 0 or 1, on the other hand, only 16.0% of the latter fulfilled PGA 0 or 1 (Fig. 2 ). 277 patients fulfilled swollen joint count, tenderness joint count, and CRP 1 or less.46.2% fulfilled Boolean-based remission, and 53.8% fulfilled three of four Boolean criteria except PGA. Mean HAQ-DI was the former 0.19, the latter 0.67, which showed a significant difference (Fig. 3 ). Cut off value was HAQ-DI=0.18 that satisfies PGA 0 or 1 by Receiver Operating Characteristic analysis of the 277 patients fulfilled swollen joint count, tenderness joint count, and CRP 1 or less (Fig. 4 ). Multivariate analysis revealed that disease duration independently predicted HAQ-DI≤0.18. Conclusions: Physical function had an impact on PGA. Physical function was associated with disease activity, especially in the early stage. Cut off value that satisfies PGA 0 or 1 was HAQ-DI =0.18, which was stringent than the HAQ remission (≤0.5). Given that HAQ-DI was getting worse in correlation with disease duration, and disease duration independently predicted HAQ-DI≤0.18, early aggressive treatment is needed to achieve functional remission. References: Studenic P, Smolen JS, Aletaha D. Near Misses of ACR/EULAR criteria for remission: effects of patient global assessment in Boolean an index-based definitions. Ann Rheum Dis 2012;71:1702-1705 Studenic P, Radnner H, Smolen JS, Aletaha D. Discrepancies between patients and physicians in their perceptions of rheumatoid disease activity. Arthritis Rheum 2012;64:2814-2823 Strand V, Khanna D. The impact of rheumatoid arthritis and treatment on patients' lifes. Clin Exp Rheumatol 2010;28:S32-40 Disclosure of Interest: T. Watanabe Speakers bureau: Janssen Pharmaceutical, T. Kojima Grant/research support from: Takeda Pharma Corporation, Janssen Pharmaceutical, and Astellas Pharma Corporation, Speakers bureau: Mitsubishi Tanabe Pharma Corporation, Takeda Pharma Corporation, Eisai Pharma Corporation, N. Takahashi: None declared, K. Funahashi: None declared, S. Asai Speakers bureau: Eisai Pharma Corporation, T. Takemoto: None declared, N. Asai: None declared, N. Ishiguro Grant/research support from: Daiichi Sankyo, Takeda Pharmaceutical, Hisamitsu Pharmaceutical, Speakers bureau: Daiichi Sankyo, Takeda Pharmaceutical, Hisamitsu Pharmaceutical, Otsuka Pharmaceutical,